Economic Impact of COVID-19 on Micro, Small and Medium Enterprises (MSMEs) in India - Agarwal, Tarunima (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The Micro, Small and Medium Enterprises (MSMEs) sector in India is contributing significantly to country’s economy and people’s livelihood. It is contributing to approximately 30% of Indian GDP. Due to Covid-19 pandemic and lockdowns, this sector has been impacted adversely but rebounded back and redefined its strategies and priorities, with the support of various government economic reforms and packages. It was examined how these disruptions manifested and how the various government policies that have been implemented over the past year, have impacted the Indian economy, through the lens of macroeconomic concepts. The MSME sector will continue to play critical role in country’s economy and therefore, deserves central attention in government policies.
Keywords: COVID-19; MSMEs; Economic impact